Molecular imaging probes for multi-spectral optoacoustic tomography - Gujrati, Vipul; Mishra, Anurag; Ntziachristos, Vasilis (Chemical Communications, 2017)
Multi-Spectral Optoacoustic Tomography (MSOT) merges the power of high-resolution imaging at tissue depths of several millimeters to centimeters with the advantages of optical imaging, in large part by exploiting spectral detection of endogenous molecules in tissue or exogenous photoabsorbing probes. Current advances in fast-tuning laser technology, image reconstruction and spectral detection schemes have yielded real-time optoacoustic (photoacoustic) imaging spanning applications from microscopy to human imaging. This progress has generated an unprecedented need for imaging probes and reporter gene approaches optimized for optoacoustic signal generation. New classes of probes are emerging and create new opportunities for visualizing morphological and pathophysiological features in vivo, in a non-invasive manner. Here we review recent progress in optoacoustic probes and discuss applications and challenges for biological imaging as well as prospects for clinical translation.
CRIS-Team Scopus Importer:2023-03-08